D8 Open Data for Agriculture Presentation by Kathleen Flaherty - Flaherty, Kathleen (2013)
D8 Open Data for Agriculture Presentation by Kathleen Flaherty, IFPRI, Agricultural Science and Technology Indicators (ASTI).